Remembering Volodymyr Vasilyovich Sharko - Libardi, Alice Kimie Miwa (Topological Methods in Nonlinear Analysis, 2015)
We lost Volodymyr Vasilyovich Sharko who passed away unexpectedly at the age of 65 on October 07, 2014 in Kiev. V. Sharko was the Deputy Director on Scientic Works at the Institute of Mathematics and a corresponding member of the National Academy of Sciences of Ukraine.